A mathematical model predicting host mitochondrial pyruvate transporter activity to be a critical regulator of Mycobacterium tuberculosis pathogenicity. (May 2017) - Mehrotra, Parul; Rao, Kanury V.S.; Chatterjee, Samrat
Abstract: Modulation of host metabolic machinery by Mycobacterium tuberculosis is a well established phenomenon. In our earlier study (Mehrotra et al., 2014 ), we observed a marked increase in acetyl-CoA levels in cells bearing virulent M. tuberculosis infections compared to host cells harbouring avirulent infections. The difference was observed inspite of similar levels of total host cellular pyruvate in both infection types. The present study aimed in capturing the cause for such a phenomenon that defines the pathogenicity of M. tuberculosis . Through mathematical model, we dissected the relative importance of virulence mediated effect on Pyruvate dehydrogenase (PDH) activity, rate of acetyl-CoA consumption and mitochondrial pyruvate transporter (MPC) activity in causing the observed outcomes. Simulation results exhibit MPC to be the key regulatory junction perturbed by virulent strains of M. tuberculosis leading to alteration of mitochondrial metabolic flux and regulation of acetyl-CoA formation. As an experimental validation, drug mediated inhibition of MPC activity was sufficient to reduce virulent bacillary loads, pointing towards a possible mechanistic target for drug discovery.